1996
DOI: 10.1128/jb.178.14.4131-4142.1996
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the Mycoplasma mycoides cluster as determined by sequence analysis of the 16S rRNA genes from the two rRNA operons

Abstract: The so-called Mycoplasma mycoides cluster consists of six species or subspecies of mycoplasmas (Mollicutes). These species are pathogenic for ruminants and some of them are of great concern in veterinary medicine. The members of the M. mycoides cluster have two rRNA operons (rrnA and rrnB). The nucleotide sequences of the 16S rRNA genes of 10 strains, representing all of the known species and subspecies of the M. mycoides cluster, were determined by direct automated solid-phase DNA sequencing. The sequences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
131
1
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(138 citation statements)
references
References 46 publications
5
131
1
1
Order By: Relevance
“…It has been reported that MmmLC and Mmc are antigenically very similar, as assessed by the numerical analysis of one-dimensional SDS-PAGE protein patterns [18]. Phylogenetic studies based on sequence analysis of 16S rRNA genes have shown that it is obviously impossible to genetically distinguish between the MmmLC biotype and the subspecies Mmc (99.9% similarity) [26]. Therefore, MmmLC and Mmc may represent two different phenotypes of a same and unique subspecies of the M. mycoides species [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that MmmLC and Mmc are antigenically very similar, as assessed by the numerical analysis of one-dimensional SDS-PAGE protein patterns [18]. Phylogenetic studies based on sequence analysis of 16S rRNA genes have shown that it is obviously impossible to genetically distinguish between the MmmLC biotype and the subspecies Mmc (99.9% similarity) [26]. Therefore, MmmLC and Mmc may represent two different phenotypes of a same and unique subspecies of the M. mycoides species [21].…”
Section: Discussionmentioning
confidence: 99%
“…Among the field strains tested in this study, five strains were proven to be strictly identical to Msp7 strain PG50 by MF dot, by PCR and on the basis that these strains shared some strictly similar IS 1296 and vmm Southern blot profiles. Most of the phylogenetic analysis [14,25,33], particularly based on the 16S rRNA sequences [26], place Msp7 strain PG50 as a sub-species of the M. capricolum species. However, other genetic particularities place Msp7 strain PG50 phylogenetically closer to the M. mycoides species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…capri and M. mycoides subsp. mycoides LC [24]. Since phylogenetic analysis based upon the 16S rRNA gene sequences alone provided only a limited understanding of species relationships and evolutionary history, and 16S rRNA operons show high intraspecific variation, sequences of protein-encoding genes have been suggested and used.…”
Section: Introductionmentioning
confidence: 99%